Eccentric or concentric exercises for the treatment of tendinopathies? - Couppe, C.; Svensson, R. B.; Grävare Silbernagel, K.; Langberg, H.; Magnusson, S. P. (Journal of Orthopaedic & Sports Physical Therapy, 2015)
Tendinopathy is a very common disorder in both recreational and elite athletes. Many individuals have recurrent symptoms that lead to chronic conditions and termination of sports activity. Exercise has become a popular and somewhat efficacious treatment regime, and isolated eccentric exercise has been particularly promoted. In this clinical commentary, we review the relevant evidence for different exercise regimes in tendinopathy rehabilitation, with particular focus on the applied loads that are experienced by the tendon and how the exercise regime may affect these applied loads. There is no convincing clinical evidence to demonstrate that isolated eccentric loading exercise improves cl inical outcomes more than other loading therapies. However, the great variation and sometimes insufficient reporting of the details of treatment protocols may hamper the interpretation of what may be the optimal exercise regime with respect to parameters such as load magnitude, speed of movement, and recovery period between exercise sessions. Future studies should control for these loading parameters, evaluate various exercise dosages, and think beyond isolated eccentric exercises to arrive at firm recommendations regarding rehabilitation of individuals with tendinopathies.